The edge of evolution : the search for the limits of Darwinism - Behe, Michael J., 1952- (New York : Free Press, 2007)
Draws on new findings in genetics to pose an argument for intelligent design that refutes Darwinian beliefs about evolution while offering alternative analyses of such factors as disease, random mutations, and the human struggle for survival.
Includes index.
Keywords: Evolution (Biology); Molecular evolution; Genetics; Intelligent design (Teleology)